Giant saccular aneurysm of the innominate artery. (11th October 2019) - Robaldo, Alessandro; Apostolou, Dimitri; Peano, Enrico; Novali, Claudio
Abstract: We report a rare case of a saccular aneurysm of innominate artery without any apparent causative history. Although the treatment choice remains debatable, due to the poor condition of the patient, the lesion was excluded by using a balloon-expandable covered stent with a satisfactory early-term outcome.